Lemyra kaikarisi, a new species from China (Lepidoptera, Erebidae, Arctiinae) - Saldaitis, Aidas; Volynkin, Anton V.; Duda, Juozas (Zootaxa, 2019)
The genus Lemyra Walker, 1856 is widely distributed in Asia. It is subdivided into two subgenera, Lemyra and Thyrgorina Walker, 1864 [1865] and includes more than 100 valid species, many of which were described during last three decades (Thomas 1990; Fang 1993; Inoue 1993; Tshistjakov & Kishida 1994; Kirti & Gill 2008; Černý 2011; 2014; Černy & Pinratana 2009; Dubatolov 2007; Kirti & Singh 2016; Saldaitis et al. 2018).